Combinatorial coding of Drosophila muscle shape by Collier and Nautilus. - Enriquez, J.; de Taffin, M.; Crozatier, M.; Vincent, A.; Dubois, L. (Developmental Biology, 2012)
The diversity of Drosophila muscles correlates with the expression of combinations of identity transcription factors (iTFs) in muscle progenitors. Here, we address the question of when and how a combinatorial code is translated into muscle specific properties, by studying the roles of the Collier and Nautilus iTFs that are expressed in partly overlapping subsets of muscle progenitors. We show that the three dorso-lateral (DL) progenitors which express Nautilus and Collier are specified in a fixed temporal sequence and that each expresses additionally other, distinct iTFs. Removal of Collier leads to changes in expression of some of these iTFs and mis-orientation of several DL muscles, including the dorsal acute DA3 muscle which adopts a DA2 morphology. Detailed analysis of this transformation revealed the existence of two steps in the attachment of elongating muscles to specific tendon cells: transient attachment to alternate tendon cells, followed by a resolution step selecting the final sites. The multiple cases of triangular-shaped muscles observed in col mutant embryos indicate that transient binding of elongating muscle to exploratory sites could be a general feature of the developing musculature. In nau mutants, the DA3 muscle randomly adopts the attachment sites of the DA3 or DO5 muscles that derive from the same progenitor, resulting in a DA3, DO5-like or bifid DA3-DO5 orientation. In addition, nau mutant embryos display thinner muscle fibres. Together, our data show that the sequence of expression and combinatorial activities of Col and Nau control the pattern and morphology of DL muscles.